Damage quantification in price fixing cases - López Medrano, Gabriela (2020)
Although price-fixing agreements are just one inside the group of restrictive competition practices, they are always harmful from a general economic welfare perspective because they do not admit any efficiency explanation, therefore, in terms of economic impact evaluation, the harm caused by these practices, requires a priority attention. The authors present economic concepts related to the economic harmful in price-fixing cases and brings some guidelines about estimations based on recent literature and casuistry about the anticompetitive practice’s quantification.